The role of pro-comparative advantage absorptive capacity in improving marketing performance using a resource advantage theory of competition perspective - Mahendra, Ahmad Bima; Ferdinand, Augusty Tae; Putri, Yuni Maxi (Universitas Negeri Surabaya, Indonesia, 2025)
This study aims to explain the importance of superior pro-comparative advantage absorptive capacity as a bridging concept to resolve inconsistent results regarding the role of digital marketing in improving marketing performance. The study procedures were carried out using a quantitative method with data from 290 respondents comprising owners and managers of Business-to-Business (B2B) small and medium enterprises (SMEs) in the food and beverage industry in Semarang, Indonesia. The data was obtained and analysed using structural equation model (SEM), Analysis of Moment Structure (AMOS) software. The results show that digital marketing positively affects capacity and management knowledge. Absorptive capacity positively affects both marketing performance and value co-creation, while management knowledge enhances value co-creation. Finally, value co-creation significantly contributes to marketing performance. These findings highlight the strategic importance of digital marketing and knowledge processes in driving performance outcomes. This study advances the resource advantage theory by identifying absorptive capacity as a key link between digital marketing and marketing performance. It introduces a serial mediation model involving marketing knowledge and value co-creation, offering a deeper understanding of digital strategy effectiveness.